Whole genome survey and genetic markers development of crocodile flathead Cociella crocodilus. (6th September 2021) - Zhao, R.; Lu, Z.; Cai, S.; Gao, T.; Xu, S.
Summary: Flatheads in family Platycephalidae are ecologically and commercially important marine fish species in the Indo‐West Pacific. Due to similar morphological characters, the taxonomy and phylogenetics of flatheads are in confusion. Studies on phylogenetics and molecular marker development are required to discriminate congeners of flatheads. In the present study, we performed whole genome survey sequencing of crocodile flathead Cociella crocodilus to provide genomic information and genetic markers of this species. In total, 54.03 Gb of clean genomic data were generated. The genome size was estimated to be 732.99 Mb with the heterozygosity ratio of 0.73% and the repeat sequence ratio of 33.48%. The preliminary assembled genome sequences were 794.07 Mb with contig N50 of 1504 bp. We detected 2 624 875 genome‐wide SNPs with transition/transversion ratio of 1.422. A total of 313 842 microsatellite motifs were identified, most of which were dinucleotide motifs with a frequency of 74.89%. In addition, we assembled the complete mitogenome of C .  crocodilus and subsequent phylogenetic analysis were performed. Phylogenetic analyses revealed numbers of polyphyletic groups in family Platycephalidae. The reported genomic data and genetic markers in our study should be useful in further phylogeny and phylogenomics studies of flathead species.